Investigation of Frictional Resistance Between Orthodontic Archwires and Brackets with Different Surface Coatings. (Bangladesh Journal of Medical Science, 2025)
Background A crucial component impacting the efficacy of orthodontic therapy is the frictional resistance between orthodontic archwires and brackets. Archwires with surface coatings may greatly decrease this resistance, allowing for better tooth movement with fewer side effects. In this simulated clinical investigation, the frictional resistance of orthodontic archwires and brackets with various surface coatings is investigated. Materials and Methods A total of 90 orthodontic brackets and archwires were categorized into three groups (n=30 per group) based on the surface coatings of the archwires: Group A (uncoated stainless steel), Group B (Teflon-coated stainless steel), and Group C (nano-diamondcoated stainless steel). Testing was conducted using a universal testing machine with a simulated dry environment. Frictional resistance was measured by applying a 500 g load, and the readings were recorded in Newtons (N). Results The mean frictional resistance values observed were: Group A (5.4 ± N), Group B (4.2 ± 0.5 N), and Group C (3.1 ± 0.4 N). Nano-diamond-coated archwires (Group C) exhibited significantly lower frictional resistance compared to Tefloncoated (Group B) and uncoated archwires (Group A) (p < 0.05). Conclusion Surface coatings, particularly nano-diamond coatings, significantly reduce the frictional resistance between orthodontic archwires and brackets. This finding suggests that nano-diamond-coated archwires may improve the efficiency of orthodontic treatment by reducing frictional forces. Further clinical studies are warranted to confirm these results.BJMS, Volume: 24. Supplementary Issue 2025, Page : 78-81